Screening Program for Congenital Hypothyroidism in Sukhothai Hospital. - ภิญโญพรพาณิชย์ ปรีชา (Journal of Preventive Medicine Association of Thailand, 2019)
Congenital hypothyroidism is a condition of thyroid hormone deficiency, presents at birth. This disease leads to severe intellectual disability growth development and mental retardation when the human lacks of the hormonal supportive treatment. In Thailand, congenital hypothyroidism screening program has been conducted since 1991. This screening program of Thai government, the research was conducted since 1991. This screening program has been developed for congenital hypothyroidism detection by following up from pediatricians and for the prevention of this disease by providing supplement to pregnant women at antenatal clinic. The previous study found the incidence in Northern part of Thailand was 1:1703, and babies were repeat investigated for diagnosis only 40%. This screening program was applied in Sukhothai Hospital by blood testing of TSH (Thyroid Stimulating Hormone). The cutoff point level of this hormone is 25 mIU/L. If this hormone is more than the cutoff point level in the samples, the repeating blood examination of TSH and FT (Free thyroxine) was immediately reconfirmed. The results showed that 10,610 babies was delivery after birth between 48 hr and 7 days from Sukhothai Hospital during 2010-2015, and 10,404 (98.05%) babies were included in this investigation. 13 babies were detected for Congenital hypothyroidism, and the other 3 babies were detected for transient hypothyroidism due to maternal on thyroid hormone during pregnant by physicians. It was concluded that the incidence decreased from 1:816 to 1:1981 during 5 years. This may be from the visiting of all maternal at antenatal clinic before delivery has received the iodine supplement.